Analisis Semiotika Pesan Moral dan Nilai Sosial pada Iklan Cegah Stunting Itu Penting dengan Pendekatan Kualitatif - Fito Herlambang; Lathifa Prima Ghanisyana; Ghefira Prisyilia Azzahra; Fitria, Fitria (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study uses Roland Barthes' semiotic technique to examine the social values and moral messages in the public service announcement "Preventing Stunting is Important." The study uses a descriptive qualitative approach, gathering information via key informant interviews, a review of pertinent literature, and direct observation of the commercial. Barthes' three layers of meaning—myth (ideological meaning), connotation (implied meaning), and denotation (literal meaning)—are used to analyze data. The results show that the commercial promotes moral values on the duties of parents, particularly mothers, in providing exclusive breastfeeding, maintaining hygiene, making sure pregnant women eat healthily, and seeking medical attention on a regular basis. It also emphasizes social ideals including community involvement, family collaboration, and fair access to health education. Through emotionally compelling and educational imagery, the commercial successfully raises public awareness of the risks of stunting and how to prevent it. These results suggest that visual media, especially public service announcements, have a great deal of potential for influencing public opinion and successfully conveying social messages. As a result, the semiotic technique is useful for revealing the underlying meanings concealed in mainstream media visual representations.